Corrugated Galvanised Iron Sheet as an Alternative to Conventional Roofing Materials “A case study from Sakteng Wildlife Sanctuary, Bhutan” (International Journal of Scientific Research and Management (IJSRM), 2018)
Corrugated galvanized iron (CGI) sheet as an alternative to conventional roofing material was initiated under the integrated conservation development program (ICDP) of Sakteng Wildlife Sanctuary in the year 2004. The program was aimed at reducing community pressure on natural resources to enhance conservation of biodiversity and keystone fauna and flora species through protection of wild habitat. It has benefited 628 inhabitants of Merak and Sakteng which were identified as the least developed among 15 Gewogs (Blocks) under Trashigang Dzongkhag (District). Data were collected through semi structured questionnaires to study the impact of the program to policy and natural habitat management. Amongst the two types of conventional roofing materials available in the locality, Shingles (79%) were in extensive use in comparison to Bamboo mat (21%) attributing to its durability. However, people prefer to use CGI sheet (100%) roofing which is economical, durable and effective in comparison to Shingle and Bamboo mat roofing, where incidences of water seepage to the room is frequent and requires replacing after 5.6 and 1.7 years respectively incurring higher maintenance costs. Replacing conventional roofing with CGI sheet has a long-term positive impact to conservation of forest and wild habitat. It is estimated that under ideal conditions approximately 5521 healthy matured Fir trees (>4’1’’girth) and 1.68 million Bamboos were saved from felling since the initial supply of CGI sheet. However, effective roofing has led to the construction of the illegal permanent concrete huts in the Tsamdro (pastureland) and changes in the architectural designs of their native houses. The need of proper drainage system was also observed as important to reduce the gully erosion from CGI sheet roof run-off.